2016
DOI: 10.2967/jnumed.116.174904
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of Breast Parenchymal Uptake on 18F-FDG PET/CT: Correlation with Age, Background Parenchymal Enhancement, and Amount of Fibroglandular Tissue on MRI

Abstract: Background parenchymal enhancement (BPE), and the amount of fibroglandular tissue (FGT) assessed with MRI have been implicated as sensitive imaging biomarkers for breast cancer. The purpose of this study was to quantitatively assess breast parenchymal uptake (BPU) on 18 F-FDG PET/CT as another valuable imaging biomarker and examine its correlation with BPE, FGT, and age. Methods: This study included 129 patients with suspected breast cancer and normal imaging findings in one breast (BI-RADS 1), whose cases wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 39 publications
3
19
1
Order By: Relevance
“…While many studies have explored the importance of BPU in diagnosing, staging, and following treatment therapy in breast cancer, one previously published study examined the relationship between BPU and BPE. In that study, Leithner et al found a correlation between BPU and qualitative measurements of MRI BPE. Similarly, in our study we show a correlation between qualitative assessment of BPE and BPU.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…While many studies have explored the importance of BPU in diagnosing, staging, and following treatment therapy in breast cancer, one previously published study examined the relationship between BPU and BPE. In that study, Leithner et al found a correlation between BPU and qualitative measurements of MRI BPE. Similarly, in our study we show a correlation between qualitative assessment of BPE and BPU.…”
Section: Discussionmentioning
confidence: 82%
“…Thus far, what MRI BPE really represents has not been clearly delineated. Possible increased metabolic activity was proposed by Pike and Pearce and recently shown in a single study by Leithner et al In their study, they utilized only qualitative BPE data to correlate with BPU, which can be prone to both inter‐ and intrareader variability. The purpose of this study was to use more objective 3D quantitative measurements of BPE, in addition to qualitative BPE measurement to confirm the association of BPE and BPU.…”
mentioning
confidence: 95%
“…To our knowledge, this is the first study using 18 F-FDG PET to examine patients with benign and malignant tumors for differences in BPU of the contralateral tumor-free breast. In contrast to both BPE and FGT, which are usually assessed through subjective visual estimation, BPU can be easily quantified, is highly reproducible (17,27,28), and therefore may serve as a more stable, noninvasive imaging biomarker. In a recent study that assessed the correlation and reproducibility of quantitatively measured BPU with qualitatively evaluated BPE and FGT as well as age, there were significant direct correlations between BPU and BPE, and between BPU and FGT, of the healthy contralateral breast (17), with almost perfect inter-and intrarater agreement for all parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, 141 patients (140 female; mean age, 57 6 14.3 y; range, 18-86 y) with a tumor-free contralateral breast on mammography, ultrasound, MRI, and 18 F-FDG PET/MRI (BI-RADS 1) were included in this retrospective analysis. Several patients have been previously analyzed and reported in a different context (17,19,22).…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation